Multiple Regulatory Mechanisms Control B-1 B Cell Activation - Sindhava, Vishal; Bondada, Subbarao (Frontiers in Immunology, 2012)
B-1 cells constitute a unique subset of B cells identified in several species including mice and humans. B-1 cells are further subdivided into B-1a and B-1b subsets as the former but not the later express CD5. The B-1a subset contributes to innate type of immune responses while the B-1b B cell subset contributes to adaptive responses. B-1 cell responses to B-cell receptor (BCR) as well as toll-like receptor (TLR) ligation are tightly regulated due to the cross-reactivity of antigen specific receptors on B-1 cells to self-antigens. B-1 cells are elevated in several autoimmune diseases. CD5 plays a major role in down regulation of BCR responses in the B-1 cell subset. Reduced amplification of BCR induced signals via CD19 and autoregulation of BCR and TLR responses by B-1 cell produced IL-10 appear to have a role in regulation of both B-1a and B-1b B cell responses. Siglec-G receptors and Lyn kinase also regulate B-1 cell responses but their differential role in the two B-1 cell subsets is unknown.